(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The aim of this work is to definition new type of Nano- M -continuous function. It is named Nano-M-(Nano semi, Nano pre_ , Nanoα_ , Nanoβ_ Nanoδ − Nano θ_ , Nanoθ_, Nano Re_, NanoθS _) continuous function and to reach a relationship with types of NanoM - cont function are studied with some examples, properties and necessary theorems are studied on it.